Sands of Iwo Jima - Grainger, Edmund; Dwan, Allan; Wayne, John ([S.l.] : Video Collection International, 1993)
Blazing action and spectacle are on the menu as battle-toughned Sergeant John M. Stryker (John Wayne) prepares a group of soldiers for action in the Pacific. His training methods are harsh and the man dislike him, especially new recruit Peter Conway (John Agar).
Credit : John Wayne
Copy available in DVD format.
Keywords: World War, 1939 -- 1945 -- Motion pictures and war; World War, 1939 -- 1945 -- Campaigns -- Japan